Frameworks of Reference in the Identification of Latin Dialects - Gonda, Attila (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
Various studies proved that the methodology of J. Herman produces plausible and verifiable results in the field of Latin dialectology, but certain methodological questions remained still unanswered regarding our points of reference in the decision which proportions of the data of the inscriptional faults are classified significant; how to decide on the basis of the proportion of a certain error type if a certain linguistic change was in progress, if it was completed, or if it was not active in the examined territory; which types of errors can serve as base or bases of comparison for a specific examined error type; which periods and territories should be the point of reference in comparisons. In the present study, we attempt to give answers to these questions by running statistical surveys using different points of reference in statistical significance and different bases of comparisons in the error types, and we set up a list of expected results based on the known tendencies of sound changes in Vulgar Latin against which we will measure the actual results of the survey in order to determine which methods were the most effective in meeting the expected picture that we already know about the development of Romance languages.